Designing a multi-epitope vaccine against Shigella dysenteriae using immuno-informatics approach - Qureshi, Hurria; Basheer, Amina; Faheem, Muhammad; Arshad, Muhammad Waqar; Rai, Sunil Kumar; Jamal, Syed Babar (Frontiers in Genetics, 2024)
Shigella dysenteriae has been recognized as the second most prevalent pathogen associated with diarrhea that contains blood, contributing to 12.9% of reported cases, and it is additionally responsible for approximately 200,000 deaths each year. Currently, there is no S. dysenteriae licensed vaccine. Multidrug resistance in all Shigella spp. is a growing concern.Current vaccines, such as O-polysaccharide (OPS) conjugates, are in clinical trials but are ineffective in children but protective in adults. Other vaccines include Shigella type 3 secretion system (T3SS) invasion protein antigens IpaB, IpaC, and IpaD. Thus, innovative treatments and vaccines are needed to combat antibiotic resistance. In this study, we used immuno-informatics to design a new multiepitope vaccine and identified S. dysenteriae strain SD197's membrane protein targets using in-silico methods. The target protein was prioritized using membrane protein topology analysis to find membrane proteins. B and T-cell epitopes were predicted for vaccine formulation. Screening considerations included selecting MHC class I epitopes with a predicted IC50 value of < 500 nM and a percentile rank of ≤ 1.0. Selection criteria for MHC class II epitopes included a percentile rank ≤ 10.0, anticipated IC50 value ≤ 1000 nM, antigenicity, allergenicity, and toxicity studies. Adjuvants and linkers were added to the vaccination to boost immunity. The vaccine construct's immunogenicity, physicochemical characteristics, and allergenicity were evaluated. Molecular docking was done between vaccine design 3D structure and human TLR-4 (PDB 2Z65). Normal Mode Analysis (NMA) assesses docked complicated molecular mobility.The eigenvalue was 3.925996e-07. Low eigenvalues indicate steady and flexible molecule mobility in the binding contact region. E. coli K12 strain recombinant plasmid pET-28a (+) was optimized for codons in an effective microbial expression system. Finally, the entire in-silico analysis suggests that the suggested vaccine may induce a significant immune response against S. dysenteriae, making it a promising option for additional experimental trials.